Hábitos alimentares de idosos pertencentes a grupo de convivência - Volkweis, Dionara Simoni Hermes (2013)
The extension of life expectancy have generated serious concerns about the way in which this population is envelhecendo.O successful aging has been associated with healthy eating habits, physical activity practices and consequently the best health standards. Eating habits make erroneous excess weight and should be advised and guided. In this context, the objective was to assess the dietary habits of the elderly belonging to group living, habits and compare the different genres and characterize the sociodemographic and health conditions. We evaluated 221 elderly, 149 females and 72 males, both answered the food frequency questionnaire (FFQ) that consisted of questions about food intake, and after, the foods were grouped into fibers, carbohydrates, proteins, lipids and vitamins and evaluation questionnaire, containing identification data, socio-demographic and health. By analyzing the sample in relation to food habits and compared with the genera observed that lipids are the foods eaten most often by the elderly and fiber and vitamins were the food groups that the elderly consume less, and as the characterization socio-demographic and health, most of the respondents are female, married, Catholic, with an income below the poverty level, non-practicing physical activity, do not consult with a nutritionist, and hypertensive drug user. Still, we can conclude that the data should be used to trigger a control program that feed this population are eating too much saturated fat in the diet, which can compromise a process of successful aging.